The Effect of Bacillus subtilis on Bioethanol Production from Ambon Banana (Musa paradisiaca var. sapientum Linn) Peels by Using Fermentation Process - Bilyartinus, Gaudentius; Siswanto, Anggun Puspitarini (Vocational College of Universitas Diponegoro, 2021)
The breakthrough to optimize Indonesia's energy is by utilizing abundant renewable energy sources. Its geographic location has the potential to become a country with the largest renewable energy source in the world. The potential energy that comes from vegetables is called bioethanol. Bioethanol is an organic fuel produced by bioethanol fermentation. It can be an alternative material for making sanitary products amid the increasing spread ofCOVID-19 in Indonesia.So the authors try to innovate how to use Ambon Banana (Musa paradisiaca var. sapientum Linn) peels to become bioethanol. This research aimed to investigate the effect of Bacillus subtilis in the fermentation of bioethanol production from Ambon banana peels. The methods used were pretreatment, hydrolysis, fermentation, and distillation. Bacillus subtilis and Saccharomyces cerevisiae ratio (10: 5 and 5: 5) use for obtaining high ethanol yields, as well as variations in pH 2 and 6 in the fermentation starter. The variable were designed by using Factorial Design. The result shows the yeast ratio of B. subtilis and S. cerevisiae (10: 5) resulted the highest concentration of bioethanol (6%) in 6 days. In acidic conditions (pH 2), the bacteria don’t grow optimally. The higher concentration of bioethanol (6%) was reached in pH 6.The research supports the Government Program Reducing the dependency of fossil fuels and innovation to produce sanitary product from bioethanol.